Varietal performance of transplant aman rice under different hill densities (Bangladesh Journal of Agricultural Research, 2010)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from July to December 2004 to evaluate the effect of hill spacing on the performance of BRRI dhan40 and BRRI dhan41 as Transplant aman crop. The experiment consisted of five hill spacings viz., 5cm. 10cm, 15 cm, and 25 cm where row to row spacing of 25 cm was kept constant for all treatments. The experiment was laid out in randomized complete block design with four replications. The 25 cm x 5 cm hill spacing produced the tallest plant, highest total number of tillers/hill, bearing tillers/hill lowest number of non-hearing tillers/hill, grain yield and harvest index, while 25 cm x 5 cm hill spacing produced the highest number of sterile spikelets/panicle, straw yield and biological yield. BRRI dhan41 produced higher grain yield (4.7 t/ha) which was the contribution of higher number of grains/panicle and heavier grain weight. Lower yield (4.51 t/ha) was recorded in BRRI dhan40.Key Words: Varietal performance; T. aman rice; hill density.DOI: 10.3329/bjar.v34i1.5750Bangladesh J. Agril. Res. 34(1) : 33-39, March 2009